Порванная струна: [роман] / Наталья Александрова - Александрова Наталья Николаевна (АСТ, 2009)
Экземпляры: ф. 4 (20130626) / Инвентарный номер: 99862 / Цена: 50.00 / Авт.знак: А 46 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6